O tutor virtual na formação continuada em educação especial - Mesquita, Pâmella Stefânia Picinin de [UNESP] (2015)
This educational research, of exploratory nature had a course in specialized educational assistance in the perspective of inclusive education, offered in the distance learning modality, as its setting. The study aims to investigate what the virtual tutor's say about: a) the educational and professional background needed to perform this function, as the course requires; b) the limits and possibilities of this role in courses of such nature; c) the structure and operation of the course. In order to perform these studies and meet these goals, 6 basic and/or superior education teachers who have worked as tutors in the aforementioned course took part in this survey. The data was gathered by means of semi-structured interviews carried out using the freely available Skype software as a tool for synchronic interaction. All interviews were recorded in audio using the also freely available software Audacity. The project was approved by the Ethical Committee of FFC/Unesp-Marília (Process no. 0691/2013) as being in accordance with the ethical principles stated in the resolution 196/96 (CNS). The data was analyzed by means of content analysis technique (BARDIN, 2010). Results showed that all the tutors interviewed considered their educational background adequate for this course. The participants reported they had an active role in the activities assigned to them, such as: a) follow the deadlines and support the course takers accordingly, b) give instruction as to the use of the posted course materials, c) open discussion forums, among others. Also relevant, concerning the course's structure and design, was the fact that the tutors had divergent opinions about the educational model chosen by the staff. The conclusion was that the tutor's role was strongly related to operational and technical duties underlying the course. Although distance learning is a feasible possibility of professional qualification for teachers in our country, the modes of...